World Islamic Bank Market - Azimov Obidjon Toymuratovich (Academia Open, 2026)
General Background The global Islamic banking market has emerged as a rapidly expanding segment within the international financial system, characterized by interest-free financing, risk-sharing mechanisms, and asset-backed transactions. Specific Background Over the past decade, Islamic finance has experienced significant growth, supported by increasing asset volumes, institutional development, and broader geographic participation across regions such as the Middle East, Southeast Asia, and Europe. Knowledge Gap Despite extensive reporting on asset growth and regional distribution, there remains a need for integrated analysis linking growth trends, regional concentration, and future development drivers within the global Islamic banking system. Aims This study aims to analyze the size, growth rate, and regional distribution of Islamic banking assets based on recent global financial reports. Results Findings indicate that global Islamic finance assets reached approximately USD 6 trillion, with USD 4.32 trillion attributed to Islamic banking, growing at 10.6%, primarily concentrated in MENA and GCC regions, while Southeast Asia and Africa demonstrate emerging growth potential. Novelty The study provides a consolidated perspective combining asset distribution, regional dynamics, and future sectoral trends including digital banking, sukuk markets, and sustainable finance instruments. Implications These findings suggest that Islamic banking will continue to expand globally, with diversification beyond traditional regions and increasing integration into sustainable and digital financial systems, contributing to broader financial inclusion and stability. Highlights:• Global Asset Volume Reaches USD 4.32 Trillion With Sustained Double-Digit Expansion• Regional Concentration Dominated by Middle East and Gulf Economies With Emerging Asian Markets• Future Development Driven by Digital Banking Systems and Sukuk-Based Financial Instruments Keywords: Islamic Banking Market, Islamic Finance Assets, Sukuk Market, Digital Banking, Financial Growth.